Pengembangan Aplikasi Manajemen Proyek Perusahaan Jasa Konstruksi Kecil dan Menengah berbasis Web (Studi Kasus: AMF-Haq Engineering and Consultant) - Abdullah Muhammad Farouk Hakim; Nurudin Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The project management of AMF-Haq Engineering and Consultant company still use manual ways of management. Even though, the company still seems reluctant to change the management system, because some of management software still seems expensive and hard to use. With such of situations, the company will encounter some of risks. For example, misinformation of the usage of tools and materials, ineffective tasks distribution and workers mobilization, errors in implementation of tools and materials or losing some files while the project running. These risks, obviusly will bother the company to develop to be more bigger. Therefore, the procurement of easy-to-use software with fast access is required for the company to running more effective and eficient project management's activities. The application was decided to be web-based software, because of considering the easy and fast access to web-based software with web browser in various hardware. The software may help the company to record and update any mangement things neatly and fast..